2016
DOI: 10.1016/j.neurobiolaging.2015.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Increased bone morphogenetic protein signaling contributes to age-related declines in neurogenesis and cognition

Abstract: Aging is associated with decreased neurogenesis in the hippocampus and diminished hippocampus-dependent cognitive functions. Expression of bone morphogenetic protein 4 (BMP4) increases with age by more than 10-fold in the mouse dentate gyrus while levels of the BMP inhibitor, noggin, decrease. This results in a profound 30-fold increase in phosphorylated-SMAD1/5/8, the effector of canonical BMP signaling. Just as observed in mice, a profound increase in expression of BMP4 is observed in the dentate gyrus of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 54 publications
6
40
0
Order By: Relevance
“…BMP4 overexpression significantly reduced the total number of proliferating cells as well as the number of proliferating progenitor cells in the DG compared to control mice, consistent with previous studies showing that BMP signaling causes neural stem and progenitor cells to exit cell cycle. 15, 20 Despite the reduction in hippocampal proliferation in BMP4-overexpressing mice, we did not observe an increase in depression-like behavior in these mice, which is consistent with previous studies which have shown that inhibiting hippocampal neurogenesis is not sufficient to induce a depression-like phenotype. 9, 3840 Chronic stress produces a decrease in hippocampal neurogenesis, 4143 raising the possibility that ablation of neurogenesis may increase the susceptibility to the behavioral effects of stress.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…BMP4 overexpression significantly reduced the total number of proliferating cells as well as the number of proliferating progenitor cells in the DG compared to control mice, consistent with previous studies showing that BMP signaling causes neural stem and progenitor cells to exit cell cycle. 15, 20 Despite the reduction in hippocampal proliferation in BMP4-overexpressing mice, we did not observe an increase in depression-like behavior in these mice, which is consistent with previous studies which have shown that inhibiting hippocampal neurogenesis is not sufficient to induce a depression-like phenotype. 9, 3840 Chronic stress produces a decrease in hippocampal neurogenesis, 4143 raising the possibility that ablation of neurogenesis may increase the susceptibility to the behavioral effects of stress.…”
Section: Discussionsupporting
confidence: 91%
“…At 16 days post injection, BMPRII ablation significantly increased the number of newborn neurons as assessed by the number of ZG+ cells expressing the neuronal marker NeuN (Figure 4b, c; WT 24600±2791 n=8, BMPRII KO 36424±4547 n=8, p<0.05), consistent with previous studies demonstrating enhanced maturation of NPCs into neurons in the absence of BMP signaling. 15, 20 Behavioral analysis on the TST demonstrated that ablation of BMPRII increased latency to immobility (Figure 4d; WT 54.08±5.84 n=8, BMPRII KO 79.73±9.78 n=8, p<0.05) and decreased the total time immobile (Figure 4e; WT 165±8.2 n=8, BMPRII KO 108.6±8.8 n=8, p<0.001). In the EZM, BMPRII ablation produced a trend towards an increase in the percentage of time spent in the open arms (Figure 4f; WT 29.42±2.88 n=8, BMPRII KO 36.17±2.12 n=8, p=0.08).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…BMP-2, BMP-4, and BMP-7 are expressed in the SVZ and promote astroglial lineage commitment, whereas noggin suppresses it (Lim et al 2000;Colak et al 2008). In the SGZ, exogenous expression of noggin and BMP-4, or inactivation of either BMPRIA or Smad4 show the role of BMP signaling in the regulation of quiescence and activation of neural stem cells (Bonaguidi et al 2008;Colak et al 2008;Mira et al 2010;Bond et al 2014;Meyers et al 2016). …”
Section: Forebrainmentioning
confidence: 99%